Prevalence and associated factors of self-medication among pregnant women in Sodo Town, Southern Ethiopia - Abebe, Mesfin; Gashaw, Silenat; Getahun, Dinkalem; Wassu, Wudit; Menshaw, Tiruye; Lakew, Serawit (Frontiers in Medicine, 2024)
Background: Self-medication is a widespread practice among pregnant women worldwide, with 44.55% practicing it. However, it can lead to incorrect diagnosis, inappropriate treatment, and failure to recognize contraindications. The adverse effects of self-medication are often unknown, and they pose potential risks to maternal and fetal health. This study aims to fill the gap in knowledge concerning self-medication prevalence among pregnant women in Southern Ethiopia, promoting effective strategies and interventions.Methods: A community-based cross-sectional study was conducted among 425 pregnant women in Sodo town from April to June 2021. Participants were enrolled using a two-stage sampling technique. Data were collected using a structured questionnaire and face-to-face interviews. The association between the outcome and independent variables was assessed through bivariate logistic regression analysis. Additionally, a multivariable logistic regression analysis was carried out, considering variables with an Adjusted Odds Ratio (AOR) accompanied by a 95% Confidence Interval (CI) and a p-value of less than 0.05, which were considered statistically significant.In this study, pregnant women aged 18-39 years participated with a 100% response rate. The study found that the prevalence of self-medication during pregnancy was 20.5%, with 8.2% using herbal medicine and 12.3% using conventional medicine. A history of selfmedication and first and second-trimester pregnancy were significantly associated with selfmedication. Specifically, a history of self-medication (AOR=6.31, 95% CI: 4.89, 9.91) and first and second-trimester pregnancy (AOR=3.47, 95% CI: 1.63, 7.38; AOR=2.14, 95% CI: 1.12, 4.08) were linked to a higher likelihood of self-medication.The study found that 20.5% of pregnant women engaged in self-The study revealed a significant prevalence of self-medication among pregnant women, with 20.5% reported to engage in this practice. Itmedication. It also identified a strong association between a history of self-medication before pregnancy and the likelihood of self-medicating during pregnancy. Additionally, first and second-trimester pregnancies showed increased tendencies towards self-medication. These findings underscore the need for targeted educational programs and policy interventions to mitigate the risks associated with self-medication during pregnancy, particularly in the early stages of gestation.